2018
DOI: 10.1177/1129729818793102
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of juxta-anastomotic stenoses for failing distal radiocephalic arteriovenous fistulas: Drug-coated balloons versus angioplasty

Abstract: The aim of our study is to report the results of two types (type A, type B) paclitaxel drug-coated balloon compared with standard percutaneous transluminal angioplasty in the treatment of juxta-anastomotic stenoses of mature but failing distal radiocephalic hemodialysis arteriovenous fistulas. Two groups of 26 and 44 patients treated with two different drug-coated balloon are compared with a control group of 86 treated with standard percutaneous transluminal angioplasty. A color Doppler ultrasound was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 58 publications
(119 reference statements)
0
15
0
Order By: Relevance
“…To date, multiple observational and randomized controlled studies have evaluated the use of DCBs for prolonging patency, but caution should be taken when interpreting the results due to clinical heterogeneity resulting from the non-uniform level of intervention ( 8 9 11 12 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 ). In a retrospective study in 2014, Patanè et al ( 9 ) presented a case series of 26 patients who had juxta-anastomotic radiocephalic stenosis treated using DBA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, multiple observational and randomized controlled studies have evaluated the use of DCBs for prolonging patency, but caution should be taken when interpreting the results due to clinical heterogeneity resulting from the non-uniform level of intervention ( 8 9 11 12 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 ). In a retrospective study in 2014, Patanè et al ( 9 ) presented a case series of 26 patients who had juxta-anastomotic radiocephalic stenosis treated using DBA.…”
Section: Discussionmentioning
confidence: 99%
“…The results appeared excellent, with TLPP rates at 6 months, 1 year, and 2 years of 96.1%, 90.9%, and 57.8%, respectively, and TLSP rates at 1 year and 2 years of 100% and 94.7%, respectively. In a recent retrospective report by the same team ( 28 ), two groups of 26 and 44 patients treated with two different DCBs were compared with a control group of 86 patients treated with PBA. TLPP rates at 12 months were higher in the two DCB groups (In.Pact Amphirion, Medtronic: 90.9%; Lutonix, BD: 86.4%) than in the PBA group (62.8%, p = 0.002).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, two brands of DCB versus PB were compared in patients with juxta-anastomotic stenosis of mature but failing distal radiocephalic AVFs and all patients treated with DCB-PTA had statistically significantly higher primary patency, TLPP, secondary patency, and target lesion secondary patency rates. 33 The aforementioned study is the first scientific study using an homogeneous population and evaluating only autogenous native mature radiocephalic AVFs and stenosis of the juxta-anastomotic region for 12 months. In a randomized study comparing DCB-PTA versus PB-PTA, however, no significant difference was found in the anatomic success rates between the DCB and PB groups (89.9% vs 78.3%; p = 0.13) and both groups achieved 100% clinical success, although the restenosis rate at 6 months was 34.0% in the DCB group and 62.9% in the PB group (p = 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 68 articles were submitted to full-text review. Ultimately, 12 articles [13][14][15][16][17][18][19][20][21][22][23][24] comprising 979 patients met the selection criteria and were included in the current meta-analysis ( Figure 1). Characteristics of all included studies are summarized in Table 1.…”
Section: Study Selectionmentioning
confidence: 99%
“…Of the 11 studies [13][14][15][16][17][18][19][21][22][23][24] reporting 12-month TLR in each group (Figure 2B), the pooled rates for DCBA and BA were 43.5% (141/324) vs 63.4% (232/366), respectively. The pooled OR was 0.45 (95% CI 0.21 to 0.97, Z=2.03, p=0.04), reflecting significant reduction in 12-month TLR for DCBA.…”
Section: Target Lesion Revascularizationmentioning
confidence: 99%